Integrating Advanced Physics and Medical Physics: Innovations in Imaging and Radiation Therapy for Personalized Cancer Treatment - Hashim, Ridha Saad Muhammad; Hassan, Zainab Musa Na’amh Abd Al; Zghair, Jawad Kadhim Abdullah; Karim, Zahraa Hayder Shakir; Latif, Noor Adnan Ghaleb Abdul (American Journal of Botany and Bioengineering, 2025)
The integration of advanced physics into medical physics has significantly enhanced cancer imaging and radiation therapy, leading to more personalized and effective treatments. However, challenges remain in optimizing imaging techniques and radiation dose delivery for individualized patient care. This study explores innovations in medical imaging and radiotherapy, focusing on computational models, multi-modal imaging, and advanced radiation response modeling. Findings indicate that integrating patient-specific imaging data with computational physics enhances treatment precision, reduces radiation toxicity, and improves patient outcomes. The results emphasize the importance of interdisciplinary collaboration in medical physics to further refine personalized cancer treatment strategies, paving the way for cost-effective and adaptive therapy approaches.